The tryphosine genus Cheirimedon in Australian waters (Crustacea, Amphipoda, Lysianassidae, Tryphosinae) - Kilgallen, N.m.; Lowry, J.k. (Zootaxa, 2015)
The genus Cheirimedon is reviewed and the monotypic genus Tryphosoides placed in its synonymy. We describe fourteen new species of Cheirimedon, all from Australian waters, bringing the total number of species in the genus to 22. Full synonymies and distribution data are provided for all taxa. A key to the world species is provided.